Décoloniser l’histoire occidentale : Les naissances politiques de l’anthropologie historique - Misgav Har-Peled (L'Atelier du CRH)
One wonders why Jacques Le Goff has used the term anthropology instead of ethnology or ethno-history which could equally reflect his intellectual approach. If we consider the political dimension of the original gesture in historical anthropology, we see that it is an effort to give a history to the subjects who were considered without history. As for Levi Strauss for historians, anthropology was involved in the effort of decolonization and of integrating it in social sciences.